2022
DOI: 10.3389/fnagi.2022.843122
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Direct Current Stimulation May Reduce Prefrontal Recruitment During Dual Task Walking in Functionally Limited Older Adults – A Pilot Study

Abstract: IntroductionTranscranial direct current stimulation (tDCS) targeting the left dorsolateral prefrontal cortex (dlPFC) improves dual task walking in older adults, when tested just after stimulation. The acute effects of tDCS on the cortical physiology of walking, however, remains unknown.MethodsIn a previous study, older adults with slow gait and executive dysfunction completed a dual task walking assessment before and after 20 min of tDCS targeting the left dlPFC or sham stimulation. In a subset of seven partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 36 publications
(47 reference statements)
0
1
0
Order By: Relevance
“…In the above-mentioned studies, L-DLPFC was the main target area as it is highly related to executive function (Zhou et al, 2014). A combined tDCS and functional near-infrared spectroscopy study revealed lower oxygenated hemoglobin response in the left prefrontal cortex within DT condition after 2 mA, 20 min tDCS over L-DLPFC was applied, suggesting that L-DLPFC tDCS modulates the prefrontal recruiting, and the reduction of DTC may be due to the reduced oxygen consumption (Jor'dan et al, 2022) as neuroimaging study which mentioned above reported a higher activation in the healthy elderly during DT condition. Compared to tDCS over the right DLPFC or sham stimulation, anodal tDCS over the L-DLPFC can significantly enhance executive functions within conflict-related tasks (Dubreuil-Vall et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In the above-mentioned studies, L-DLPFC was the main target area as it is highly related to executive function (Zhou et al, 2014). A combined tDCS and functional near-infrared spectroscopy study revealed lower oxygenated hemoglobin response in the left prefrontal cortex within DT condition after 2 mA, 20 min tDCS over L-DLPFC was applied, suggesting that L-DLPFC tDCS modulates the prefrontal recruiting, and the reduction of DTC may be due to the reduced oxygen consumption (Jor'dan et al, 2022) as neuroimaging study which mentioned above reported a higher activation in the healthy elderly during DT condition. Compared to tDCS over the right DLPFC or sham stimulation, anodal tDCS over the L-DLPFC can significantly enhance executive functions within conflict-related tasks (Dubreuil-Vall et al, 2019).…”
Section: Discussionmentioning
confidence: 99%